A Systematic Review of Literature on Methodologies, Practices, and Tools for Programming Teaching - Borges, R. P.; Oliveira, P. R. F.; da R. Lima, R. G.; de Lima, R. W. (Revista IEEE América Latina, 2018)
It has been frequent the discussion about the teaching and learning of Programming, from the initial series to the undergraduate courses. It is noticed that many students have difficulty to learn programming by several reasons: methodology, tools, programming languages, lack of programming logic in basic education, motivation, among others. Thus, this carries out a survey of the state of the art of existing and documented approaches in the literature, through a mapping of published works in the last five years (2012 to 2016) in two of Brazil's leading scientific computing platforms (CEIE and RENOTE), whose focus is to present solutions that address methodologies and tools that can be used in the different teaching modalities. As methodology was used the Systematic Review of Literature. As a result, it was found that, although studies still focus on higher education, in recent years there has been an increasing interest in programming teaching projects for children and teenagers, using gamification and tools such as Scratch. The results also demonstrate the growing interest of researchers in the search for approaches that provide better results in this area.